(untitled) (Global Journal of Management and Business Research, 2015)
Impulsive buying behavior can be considered as a way of increasing profit of marketers. Nowadays, the popularity of electronic commerce has gained more attention from researchers and marketers as well. Hence, studying the causes of online impulsive buying behavior is necessary as such study may generate certain innovative ideas or strategies to marketers to increase profit from online market. In this study, the author emphasizes on internal factors (e.g., psychological approach) and external factors (e.g., situational, product and website factors) in studying the impulsive buying behavior. The external factors (e.g., website designs) and internal factors (e.g., affective states) which cause impulsive purchase are interrelated in certain aspects and are hard to separate individually.